2022
DOI: 10.1021/acs.iecr.1c04075
|View full text |Cite
|
Sign up to set email alerts
|

A Multiprocess Joint Modeling Method for Performance Prediction of Nonlinear Industrial Processes Based on Multitask Least Squares Support Vector Machine

Abstract: Developing the models of multiple processes rapidly and accurately is very important for process control and optimization in industrial production. This paper proposes a multiprocess joint modeling method to establish the models of multiple industrial processes simultaneously. Under the assumption that the related processes shared common information, this method views the process model as the combination of the common feature model and the special feature model. Through the full mining and using the shared inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…For example, multi-grade processes, [30][31][32] multiple distillation columns, 33 multiple compressors. 34 These systems often have the same model structure with different parameters due to the similarity of physical principles. That is, they have the same parameter sparsity properties.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, multi-grade processes, [30][31][32] multiple distillation columns, 33 multiple compressors. 34 These systems often have the same model structure with different parameters due to the similarity of physical principles. That is, they have the same parameter sparsity properties.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In practical industrial processes, there are often multiple similar systems that need to be identified simultaneously. For example, multi‐grade processes, 30‐32 multiple distillation columns, 33 multiple compressors 34 . These systems often have the same model structure with different parameters due to the similarity of physical principles.…”
Section: Introductionmentioning
confidence: 99%